Evaluation of the Oil Fiscal Regime in Russia and Proposals for Reform - Goldsworthy, Brenton (IMF Working Papers; Working Paper ;, 2010)
Oil revenue plays a central role in Russia's economic development. Thus, the recent decline in oil production and investment, and the possible contribution of the current fiscal regime to these developments, have prompted a reassessment of the oil tax system in Russia. Some important changes have already been made, while others are underway. This paper uses a simulation model to evaluate Russia's current oil fiscal regime. Based on these simulations, the paper proposes ways to make the fiscal regime more supportive of investment, while ensuring an appropriate share of oil sector profits for the government.